Influence of Narrow Rectangular Channel (AR=1:4) on Heat Transfer and Friction for V- and W-Shaped Ribs in Turbine Blade Applications - Karthik Krishnaswamy; Suresh Sivan; Hafiz Muhammad Ali (International Journal of Photoenergy)
Effective cooling of blades with a nominal pressure drop is essential for performance augmentation and thermal management of gas turbines. Hence, present work is aimed at determining the heat transfer enhancement and friction for W- and V-shaped ribs inside a rectangular cooling channel having hydraulic diameter (Dh) of 0.048 m and aspect ratio (AR) 1 : 4. Ribs are fixed facing downstream with angle of attack (α) 45° on opposite walls. Pitch (P) between two successive ribs is 25 mm for both cases. Continuous V- and W-shaped ribs with height to channel hydraulic diameter ratio (e/Dh) 0.052 and 0.0416 and pitch to height ratio (P/e) 10 and 12.5, respectively, have been examined for Reynolds number (Re) range 20000-80000. Heat transfer augmentation achieved at Re 80000 is 1.94 and 1.8 times higher than Re 20000 for V- and W-shaped ribs, respectively. Streamwise and spanwise variations in local Nusselt number ratio are highest for V-shaped ribs, which are estimated to be 31% and 12%. For W-shaped ribs, variations are 17.5% and 3.5%. Nusselt number (Nu) is highest along span length 0.5w for V-shaped ribs due to dominance of apex induced secondary flow. For W-shaped ribs, Nusselt number along the span lengths is found to be nearly same view uniformity in secondary flow. Maximum enhancement (Nu/Nuo) estimated for both the rib shapes is 3.9 at Re 20000. Due to increased rib height, friction losses for V-shaped ribs are higher than W-shaped ribs. Maximum friction loss increment is estimated to be 85% for V-shaped ribs and 42% for W-shaped ribs between Re 20000 and 40000. For both rib shapes, impact of ribs is found to be greatest at Re 40000. Thermohydraulic performance (THP) for W-shaped ribs is superior to V-shaped ribs. Best THP achieved for W- and V-shaped ribs are 3.7 and 3.4 at Re 20000.